Do Desencanto à Esperança: narrativas de experiência de inclusão vividas por estudantes de Pedagogia na prática do estágio - Rodrigues, Airton (2022)
The experiences and perceptions perceived during the internship period by Pedagogy undergraduate students have proven to be a moment of extreme complexity when given follow-up with students called disabled. These introduce into the public school system in São Bernardo do Campo - SP city due to current Federal Legislation, Lei 13.146/15, known as "Inclusion Law." The legal order makes these subjects compulsory entry into the regular education network. Such perceptions occur specifically concerning the difficulties female undergraduates face, which are related to the theories presented in the Inclusive Education subject and its practical application offered in the higher education institution during the course versus the reality experienced in the classroom. Considering the possibility of the pedagogy students' reflection about the internship processes with disabled students, as a research problem, answers to the following question it's needed: What perceptions come from the pedagogy students' narratives when they reflect on their internship processes with disabled students? What impacts does Municipal Legislation bring to inclusion students? This research purpose is to present and discuss the narratives of the student's experiences in training processes during the internship practice, the distortions genesis observed and reported between theory and its practice developments outcome. Divided into five chapters, the thesis begins with the researcher's journey, distinguishing experience from living, handling inclusive education, its advances, its paradoxes, and deepening the correlation between method and methodology. It also explores the pedagogy internship and the theory of the ideal in real experience; concludes with the opening of the experiences provided by a narrative thought identity. This study basis on the qualitative exploratory approach. The narrative research modality developed by Clandinin and Connelly (2015), in the autobiographical perspective from the perceptions of Ferrarotti (2010), and Josso (2010), directly involves the investigation and formation of a bond between the researcher and the participants, a factor that enabled the exchange of experiences and results obtained. The narratives' interpretations were supported by the studies of Paul Ricoeur (2002) and Heidegger (2015) with other hermeneutic theorists, enabling better experiences of understanding and the reflections achieved in the subjects inserted in inclusive education. This work carries out with the support of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brazil (CAPES) - Funding Code 001. (AU)